Early Years Students’ Relationships with Mathematics (Alberta Journal of Educational Research, 2016)
Early years mathematics experiences have been shown to be a significant predictor for students’ school readiness and future mathematics achievement. Previous research also indicates an important connection between emotion and mathematics learning. How do students in early years education in Alberta describe their emotional relationship with mathematics? This article documents the findings of our research focusing on Kindergarten to Grade 2 students. Our analysis showed that many students in the early years, including those at the Kindergarten level, recognized what is considered to be mathematics but mainly associated mathematics with number and numerical operations. The majority of these students reported positive relationships with mathematics, though some described negative relationships with school mathematics learning.Les expériences préscolaires avec les mathématiques se sont avérées être des prédicteurs importants de la maturité scolaire des jeunes enfants et de leur rendement en mathématiques à l’avenir. La recherche a également révélé un lien important entre les émotions et l’apprentissage des mathématiques. Comment les jeunes Albertains décrivent-ils leur relation émotionnelle avec les mathématiques? Cet article explique les résultats d’une recherche portant sur des élèves de la maternelle à la 2e année. Notre analyse démontre que plusieurs jeunes élèves, y compris ceux de la maternelle, ont reconnu ce qui est considéré comme étant les mathématiques, mais que pour eux, les mathématiques sont surtout liés aux chiffres et aux opérations numériques. Alors que la plupart de ces élèves ont indiqué qu’ils avaient un rapport positif avec les mathématiques, certains ont décrit des liens négatifs par rapport à l’apprentissage des mathématiques à l’école.